O uso da bioimpressora 3D em traumatologia da face em imagens de tomografia computadorizada do Hospital de Urgência de Teresina-PI - (:unkn) unknown (Universidade Brasil, 2021)
With the advancement of technology, a new feature has gained ground, especially in the area of surgery for facial fractures: three-dimensional (3D) printing. This technique allows the scientific community to approach the authenticity that the images present with better clarity, facilitating the diagnosis of medicine. Bioprint templates can be used for preoperative preparation, such as a template to establish implantable devices, eg cartilage and bone tissue to produce a biological template according to the needs of each patient, thus reducing the likelihood of rejection. Therefore, this work aims to analyze through the cross-sectional and experimental methodology the use of a 3D Bioprinter and 3D Printer of a computed tomography exam in the reconstruction of facial trauma occurred in patients at the Hospital de Urgência de Teresina/PI. A virtual model was created by CAD software in STL format, later the model was "sliced" to GCODE file. For the use of the 3D Bioprinter, tests were carried out with several types of materials, such as polycaprolactone (PCL), laponite, in addition to variations in pressure, temperature and speed parameters. Therefore, the Bioprinter was used to print the graft prototype obtained with PCL and solvent. The Laponite clay used in another impression through the 3D Bioprinter, for having a hydrophilic characteristic, had a visual aspect in the form of a gel in an aqueous solution. The facial trauma graft printed on a 3D Printer with Lactic Polyacid (PLA) presented a morphology compatible with the STL model obtained through tomography images, being an advantage of the FDM technique, as it is possible to create structures with pore and porosity geometries controllable and reproducible.
Keywords: Bioimpressora; Policaprolactona; Solvente; Laponita; Poliácido láctico; CS